'Form is easy, meaning is hard' revisited: (re) characterizing the strengths and weaknesses of language in children with autism spectrum disorder. Issue 4 (6th March 2017) - Naigles, Letitia R.; Tek, Saime
Abstract : Children with autism spectrum disorder (ASD) demonstrate impairments in social interaction and communication, and in repetitive/stereotypical behaviors. The degree to which children with ASD also manifest impairments in structural language—such as lexicon and grammar—is currently quite controversial. We reframe this controversy in terms of Naigles' (Naigles, Cognition 2002, 86: 157–199) 'form is easy, meaning is hard' thesis, and propose that the social difficulties of children with ASD will lead the meaning‐related components of their language to be relatively more impaired than the form‐related components. Our review of the extant literature supports this proposal, with studies (1) reporting that children with ASD demonstrate significant challenges in the areas of pragmatics and lexical/semantic organization and (2) highlighting their good performance on grammatical assessments ranging from wh‐questions to reflexive pronouns. Studies on children with ASD who might have a co‐morbid grammatical impairment are discussed in light of the absence of relevant lexical‐semantic data from the same children. Most importantly, we present direct comparisons of assessments of lexical/semantic organization and grammatical knowledge from the same children from our laboratory, all of which find more children at a given age demonstrating grammatical knowledge than semantic organization. We conclude with a call for additional research in which in‐depth grammatical knowledge and detailed semantic organization are assessed in the same children. WIREs Cogn Sci 2017, 8:e1438. doi: 10.1002/wcs.1438 This article is categorized under: Linguistics > Language Acquisition Linguistics > Language in Mind and Brain Neuroscience > Development Abstract : A child watches the shape bias intermodal preferential looking (IPL) video at home. Unlike typically developing children, children with autism spectrum disorder (ASD) do not consistently extend labels to objects of the same shape; however, these same children with ASD perform well with IPL videos assessing grammatical knowledge.